Forest conversion is more strongly associated with soil microbial functioning than chronic trace element exposure in an industrialized coastal mediterranean ecosystem - S. Fabian Plaza; F. Gonzalo Tortella; Giovanni Larama; Rodrigo Rodriguez; Thierry Lebeau; Clémentine Lapie; Walter Valdivia; Eros Fajardo; M. Fernández-Baldo; Juan Hirzel; Gustavo Santoyo; Mauricio Schoebitz (Environmental Pollution, 2026)

First report of Angiostrongylus vasorum parasitizing lesser grison (Galictis cuja) (Mustelidae) in Brazil - Julia Somavilla Lignon; Maiza Paixão Souza; Natália Büttenbender; Pedro Almeida Rezende; Raqueli Teresinha França; Kauê Rodriguez Martins; Rodrigo Casquero Cunha; Felipe Geraldo Pappen; Diego Moscarelli Pinto (Veterinary Research Communications, 2026)
Angiostrongylus vasorum is a metastrongylid nematode that parasitizes the pulmonary arteries and right heart of canids, being the etiological agent of canine angiostrongylosis, a disease of growing veterinary concern due to its expanding geographic distribution and the involvement of domestic and wild hosts. In Brazil, the parasite has been reported mainly in domestic dogs and some wild canids, and its occurrence in mustelids has been documented only once previously. This study reports the first occurrence of A. vasorum infecting a lesser grison ( Galictis cuja ) in Brazil. The mustelid was found after being accidentally run over by a vehicle on a highway in the south of the country. Clinical, physical, and complementary examinations were performed for clinical screening. In the parasitological examination of feces, nematode larvae were recovered and identified morphometrically and molecularly through conventional PCR targeting to the COX1 gene, followed by sequencing and phylogenetic analysis. The results confirmed the presence of A. vasorum , showing 99–100% identity with sequences of the same species deposited in GenBank. Therefore, we document here the first report of A. vasorum parasitizing G. cuja . Thus, the number of known host species parasitized by this helminth is expanded. Furthermore, we provide a new molecular sequence, contributing to the knowledge of this nematode in South America.

Histopathological patterns of bovine tuberculosis in cattle slaughtered in Southern Brazil: correlation with molecular detection of Mycobacterium spp - Taina dos Santos Alberti; Kauê Rodriguez Martins; Virgilio Zoppi Lemos; Clairton Marcolongo-Pereira; Marta Santos de Moraes; Margarida Buss Raffi; Rodrigo Casquero Cunha; Eliza Simone Viégas Sallis (Veterinary Research Communications, 2026)
Bovine tuberculosis (bTB) is a chronic infectious disease caused by Mycobacterium bovis , which has major veterinary, economic, and zoonotic relevance. This study aimed to characterize the histopathological patterns of bTB lesions and their association with molecular detection in cattle slaughtered in Southern Brazil. Thirty-six tissue samples with lesions suggestive of bTB were collected during municipal inspection in Pelotas, Rio Grande do Sul. Polymerase chain reaction (PCR) targeting the 16 S rRNA gene was used to detect Mycobacterium species. DNA in 35/36 samples (97.2%), whereas Ziehl–Neelsen (ZN) staining revealed acid-fast bacilli in 23/36 cases (61.1%), a statistically significant difference (McNemar’s exact test, p = 0.0018). Grossly, the lesions ranged from caseous nodules to purulent and cavitary forms. Histologically, two main morphological patterns were identified: classical granulomatous lesions with complete fibrous encapsulation (19/36, 52.8%) and disorganized granulomatous inflammation lacking complete encapsulation (17/36, 47.2%). Multinucleated giant cells were present in all ZN-positive cases, whereas neutrophilic infiltration was significantly more frequent in disorganized lesions than in classical granulomas (Fisher’s exact test, p = 0.0002), suggesting active inflammation and impaired granuloma containment. PCR showed higher sensitivity than ZN staining, detecting mycobacterial DNA even in lesions with a low bacillary load. As the assay targeted the 16 S rRNA gene, results were reported as Mycobacterium spp., and species-specific methods would be required for the definitive identification of M. bovis . These findings reinforce the diagnostic value of combining histopathology and molecular methods and emphasize the importance of recognizing atypical lesion patterns for the accurate detection of bovine tuberculosis in slaughterhouse surveillance systems.

Regional patterns of environmental variability in mangrove ecosystems along the southeastern Brazilian coast - Marcelo Antonio Amaro Pinheiro; Luis Felipe de Almeida Duarte; Caio Rodrigues Nobre; Esli Emanoel Domingues Mosna; Rodrigo dos Santos Rodriguez-Lopes; Todor Petkov; Aleksandar Dimitrov; Dimitrinka Ivanova (Regional Studies in Marine Science, 2026)

Commercial graphene oxides show distinct suitability for silver-nanocomposite formation and antibiofilm activity and cytocompatibility - Thamyres Freire da Silva; Francisco Fábio Pereira de Souza; Thiago Alves de Moura; Luciano Ferreira de Almeida; Maria Rosiene Antunes Arcanjo; Antônio Gomes de Souza Filho; Adriano Lincoln Albuquerque Mattos; Juan Antonio Cecilia; Enrique Rodriguez-Castellon; Henry Kobs; Andreia Fonseca de Faria; Maria Kelva do Carmo; et al. (In vitro models, 2026)

Impact of specific genetic polymorphisms on pork quality in Argentinian swine populations - Viviana Rita Rodriguez; Rodrigo Maximiliano Barragan; Rodrigo Peralta; Romina Maria Fabre; Mariana Lagadari (Tropical Animal Health and Production, 2026)

Comprehensive thermochemical assessment of pear waste pyrolysis for energy recovery: Insights into decomposition kinetics, gas evolution, and product characterization - Rodrigo Torres-Sciancalepore; Andrés Reyes-Urrutia; Rosa Rodriguez; Gastón Fouga; Germán Mazza (Journal of Environmental Chemical Engineering, 2026)

Assessment of spaceborne and airborne lidar metrics using Fay-Herriot models to support forest biomass estimation - Bernardo González Mesquida; Adrian Pascual; Francisco Rodriguez-Puerta; Juan Guerra-Hernández; Ryan L. Perroy; Rodrigo García-Gómez; Francisco Mauro (Forest Ecology and Management, 2026)

Modulatory Role of Oral GHRP-6 in the Immune Response and Digestive Enzyme Function in Juvenile Tilapia (Oreochromis sp.) Challenged with Pseudomonas aeruginosa - Liz Mariam de Armas; Adrian Rodríguez-Gabilondo; Liz Hernández; Ernesto A. Quintana; Alejandro J. Campos; Noelia N. Pérez; Danielle Reyes; Antonio Morales; Osmany Rodrigo; Yaima González; Leandro Rodriguez-Viera; Mario Pablo Estrada; et al. (Fishes, 2026)
Aquaculture has been established as a sustainable alternative to traditional fisheries, which face challenges such as overexploitation and environmental degradation. However, disease outbreaks, often caused by poor farming conditions, pollution, and environmental stress, remain a major concern, leading to economic losses and increasing the risk of antibiotic resistance due to the overuse of antibiotics. Therefore, it is crucial to seek new strategies that improve fish health and well-being, preventing drug resistance and promoting sustainable practices. GHRP-6, a synthetic growth hormone-releasing peptide that mimics ghrelin, has shown potential immunostimulatory properties and feed efficiency in fish. In this study, we evaluated the effects of orally administered GHRP-6 in an oil-based formulation on juvenile tilapia (Oreochromis sp.) challenged or unchallenged with Pseudomonas aeruginosa. We assessed its influence on immune gene expression and digestive enzyme activity. The results demonstrated that GHRP-6 treatment significantly enhanced growth performance (weight and length), reduced in vivo bacterial load after infection, and modulated key genes related to innate and adaptive immunity in the gills, intestine and head kidney. In addition, our results demonstrated, for the first time, a direct link between a growth hormone secretagogue in fish and the modulation of specific enzyme activity in the gut following a bacterial challenge. These findings highlight the potential of GHRP-6 as a dietary immunomodulator and growth promoter in fish farming, offering a promising strategy to reduce antibiotic usage and promote more sustainable aquaculture practices.

An expert elicitation approach for characterizing marine mammal and small-scale fisheries interactions: Insights from Chilean dolphin (Cephalorhynchus eutropia) bycatch - Stefan Gelcich; Rodrigo A. Estévez; Cayetano Espinosa-Miranda; Valentina Rebolledo-Zelada; Jorge Guerra; Sonja Heinrich; Carol Medrano; Carlos Olavarría; Cristopher Rodriguez-Jaramillo; Macarena Santos-Carvallo; Maritza Sepúlveda; María José Pérez-Álvarez (Ocean & Coastal Management, 2026)

Impact of different management practices on tree biomass and carbon dynamics 30 years after logging in eastern Amazon - Edson Vidal; Nathalia Sousa Braga; Daigard Ricardo Ortega Rodriguez; Vitoria Duarte Derisso; Rodrigo Costa Pinto; Jéssy Anni Vilhena Senado; Jonathan William Trautenmüller (Journal of Environmental Management, 2026)

The Missing Global South in Climate Change Biology: Towards Equitable Knowledge Inclusion for Effective Global Solutions - Wesley Dáttilo; Rodrigo Beas‐Luna; Alma Mendoza‐Ponce; Angela Nava‐Bolanos; Angela P. Cuervo‐Robayo; Carolina Ureta; Constantino Gonzalez‐Salazar; Cuauhtemoc Saenz‐Romero; Daniel Jimenez‐Garcia; David A. Prieto‐Torres; Eduardo Cuevas; Gabriela Castano‐Meneses; et al. (Global Change Biology, 2026)
Over the last decades, climate change biology has become a central field in global science, yet knowledge production and its inclusion in global strategies remain profoundly unequal. Our bibliometric analysis of over 580,000 records shows that ~80% of author affiliations come from Global North institutions, meaning that research agendas, theoretical frameworks, and priorities are still largely shaped outside the regions with the highest biodiversity and greatest vulnerability to climate change. This imbalance reflects structural and historical inequalities that limit the ability of Global South countries to conduct autonomous research and sustain long‐term monitoring. When research and funding originate abroad, local scientists are often excluded, leading to the loss of traditional knowledge, regional perspectives, and long‐term capacity building. These dynamics leave tropical and subtropical bioregions (generally in the Global South) underrepresented in global climate knowledge. To address this imbalance, we propose six actions: invest in infrastructure and monitoring, strengthen local research networks, link funding to capacity building, promote open and equitable data access, connect science with regional policies, and foster intersectoral collaboration. We argue that truly effective climate change biology must be global, equitable, and diverse.

First molecular detection Anaplasma phagocytophilum in sheep in Brazil - Giulia Ribeiro Meireles; Julia Somavilla Lignon; Paola Renata Joanol Dallmann; Diago Dutra Lima; Tamires Silva dos Santos; Thuanne Correa Brancão; Maiza Paixão Souza; Bruno Caetano Urtassum; Kauê Rodriguez Martins; Rodrigo Casquero Cunha; Fábio Raphael Pascoti Bruhn; Felipe Geraldo Pappen; et al. (Veterinary Research Communications, 2025)

High-resolution melting analysis in veterinary medicine: a systematic review of applications and diagnostic accuracy - Oluwagbemiga Ademola Dada; Lais Goulart Ribeiro; Natalia Machado Rahal; Kauê Rodriguez Martins; Rodrigo Casquero Cunha; Odir Antonio Dellagostin (Tropical Animal Health and Production, 2025)

Optimistic climate mitigation scenario halves projected range loss in a neotropical dolphin - Rodrigo Tardin; Guilherme Maricato; Jeremy J. Kiszka; Mauricio Cantor; Israel Maciel; Gabriel Melo-Santos; Laura May-Collado; Ana Carolina Meirelles; Maria Isabel C. Gonçalves; Fábio G. Daura-Jorge; Renata S. Sousa-Lima; Yvonnick Le Pendu; et al. (Ocean & Coastal Management, 2025)

Simulating Carbon Mineralization at Pore Scale in Capillary Networks of Digital Rock - David A. Lazo Vasquez; Jaione Tirapu Azpiroz; Rodrigo Neumann Barros Ferreira; Ronaldo Giro; Manuela Fernandes Blanco Rodriguez; Matheus Esteves Ferreira; Mathias B. Steiner (Transport in Porous Media, 2025)
Predicting the geometrical evolution of the pore space in geological formations due to fluid–solid interactions has applications in reservoir engineering, oil recovery, and geological storage of carbon dioxide. However, modeling frameworks that combine fluid flow with physical and chemical processes at a rock’s pore scale are scarce. Here, we report a method for modeling a rock’s pore space as a network of connected capillaries and to simulate the capillary diameter modifications caused by reactive flow processes. Specifically, we model mineral erosion, deposition, dissolution, and precipitation processes by solving the transport equations iteratively, computing diameter changes within each capillary of the network simultaneously. Our automated modeling framework enables simulations with digital rock samples as large as (1.125 mm) $$^3$$ 3 having 125 $$×$$ × 10 $$^6$$ 6 voxels, within seconds of CPU time per iteration. As an application of the computational method, we have simulated brine injection and calcium carbonate precipitation in sandstone. For quantitatively comparing simulation results obtained with models predicting either a constant or a flow rate-dependent precipitation, we track the time-dependent capillary diameter distribution as well as the permeability of the connected pore space. For validation and reuse, we have made the automated simulation workflow, the reactive flow model library, and the digital rock samples available in public repositories.

Presence, genetic characterization, geographic distribution and associated risk factors of feline hemoplasmas in Paraguay - María Fátima Rodriguez Valinotti; Lucía Soledad Patiño; Rodrigo Mereles Achón; Magaly Martinez; Antonio Rodriguez; Rosmary Rodriguez Valinotti; Amaias Ávalos (Brazilian Journal of Microbiology, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

New records of molecular detection of hemotropic Mycoplasma spp. in road-killed wild mammals at Southern Brazil - Julia Somavilla Lignon; Diago Dutra Lima; Paola Renata Joanol Dallmann; Kauê Rodriguez Martins; Rodrigo Casquero Cunha; Diego Moscarelli Pinto; Silvia Gonzalez Monteiro; Bianca Conrad Bohm; Fábio Raphael Pascoti Bruhn (Brazilian Journal of Microbiology, 2025)

Piper saurodermus (Piperaceae), a new peltate-leaved species restricted to the tropical rainforest of southern Mexico - Andrés Ernesto Ortiz-Rodriguez; José Rodrigo Carral-Domínguez; Guadalupe Amancio; Leopoldo Hurtado-Reveles; María Fernanda Martínez-Velarde (Kew Bulletin, 2025)

Evaluation of the performance of microalgae and constructed wetlands for the reduction of toxicity organic load and pharmaceuticals from wastewaters - Fábio Rodrigo de Oliveira; Carlos Alexandre Lutterbeck; Rosana de Cassia de Souza Schneider; Adriane Lawisch Rodriguez; Carine Baggiotto; Maurício Kersting; Alexandre Rieger; Tuanne Carvalho Nunes; Guilherme Lemões Iepsen; João Vitor Frantz; Eduardo Alcayaga Lobo; Renato Zanella; et al. (Journal of Environmental Chemical Engineering, 2025)

Microplastics in the digestive tract of an endangered cetacean of the Southwest Atlantic Ocean: The franciscana dolphin - Antonella D. Padula; Ana C. Ronda; Lucas S. Rodríguez Pirani; A. Lorena Picone; Rosana M. Romano; Gisela V. Giardino; Juan Pablo Seco Pon; Rodrigo Machado; Marcela Gerpe; Diego Rodriguez; Pablo Denuncio (Marine Pollution Bulletin, 2025)

CO2-assisted gasification of Patagonian rosehip bio-wastes: Kinetic modeling, analysis of ash catalytic effects, and product gas speciation - Rodrigo Torres-Sciancalepore; Daniela Nassini; Daniela Asensio; José Soria; Rosa Rodriguez; Gastón Fouga; Germán Mazza (Journal of Environmental Chemical Engineering, 2024)

Nucleic acid-loaded poly(beta-aminoester) nanoparticles for cancer nano-immuno therapeutics: the good, the bad, and the future - J. Rodrigo Magaña Rodriguez; Marta Guerra-Rebollo; Salvador Borrós; Cristina Fornaguera (Drug Delivery and Translational Research, 2024)
Immunotherapy has emerged as a promising approach to cancer treatment, offering improved survival rates and enhanced patients’ quality of life. However, realizing the full potential of immunotherapy in clinical practice remains a challenge, as there is still plenty of room for modulating the complexity of the human immune system in favor of an antitumor immunogenicity. Nanotechnology, with its unique properties, holds promise in augmenting the efficacy of cancer immunotherapies in biotherapeutic protection and site- and time-controlled delivery of the immune modulator biologicals. Polymeric nanoparticles are promising biomaterials among different nanocarriers thanks to their robustness, versatility, and cost-efficient design and production. This perspective paper overviews critical concepts in nanometric advanced delivery systems applied to cancer immunotherapy. We focus on a detailed exploration of the current state of the art and trends in using poly(beta-aminoester) (pBAE) polymers for nucleic acid-based antitumor immunotherapies. Through different examples of the use of pBAE polymers reported in the literature, we revise the main advantages these polymers offer and some challenges to overcome. Finally, the paper provides insights and predictions on the path toward the clinical implementation of cancer nano-immunotherapies, highlighting the potential of pBAE polymers for advancements in this field. Graphical abstract

FreshLanDiv : A Global Database of Freshwater Biodiversity Across Different Land Uses - Minghua Shen; Roel van Klink; Alban Sagouis; Danielle K. Petsch; Deborah Atieno Abong'o; Janne Alahuhta; Salman Abdo Al‐Shami; Laura Cecilia Armendáriz; Mi‐Jung Bae; Tiago Octavio Begot; Jerome Belliard; Jonathan Peter Benstead; et al. (Global Ecology and Biogeography, 2024)
Motivation Freshwater ecosystems have been heavily impacted by land‐use changes, but data syntheses on these impacts are still limited. Here, we compiled a global database encompassing 241 studies with species abundance data (from multiple biological groups and geographic locations) across sites with different land‐use categories. This compilation will be useful for addressing questions regarding land‐use change and its impact on freshwater biodiversity. Main Types of Variables Contained The database includes metadata of each study, sites location, sample methods, sample time, land‐use category and abundance of each taxon. Spatial Location and Grain The database contains data from across the globe, with 85% of the sites having well‐defined geographical coordinates. Major Taxa and Level of Measurement The database covers all major freshwater biological groups including algae, macrophytes, zooplankton, macroinvertebrates, fish and amphibians.

Development and characterization of a novel variant of long-acting bovine follicle-stimulating hormone (brscFSH) - Oscar Ignacio Cabeza; Natalie Parra; Rita Cerro; Rodrigo Mansilla; Roxana Zuniga Sanchez; Miguel Gutierrez-Reinoso; Eduardo H. Escribano; Raul Castillo; Lleretny Rodriguez-Alvarez; Kaio Tavares; Saul Gaudencio; Leonardo Martins; et al. (Theriogenology, 2024)

Geotechnologies on the phosphorus stocks determination in tropical soils: General impacts on society - Jorge Tadeu Fim Rosas; José A.M. Demattê; Nícolas Augusto Rosin; Bruno dos Anjos Bartsch; Raul Roberto Poppiel; Heidy Soledad Rodriguez-Albarracin; Jean Jesus Macedo Novais; Paulo Sergio Pavinato; Yuxin Ma; Danilo César de Mello; Marcio Rocha Francelino; Marcelo Rodrigo Alves (Science of The Total Environment, 2024)

Pharmacokinetics and safety of LEAD-452, an EGFR-specific 4-1BB-agonistic trimerbody in non-human primates - Rocío Navarro; Susana Frago; Oana Hangiu; Ainhoa Erce-Llamazares; Rodrigo Lázaro-Gorines; Miguel A. Morcillo; José L. Rodriguez-Peralto; Laura Sanz; Marta Compte; Luis Alvarez-Vallina (Toxicology and Applied Pharmacology, 2024)

Fishing and recording dead fish by citizen scientists contribute valuable data on south American ray-finned fish diversity - Lucas Rodriguez Forti; José Luís Costa Novaes; Milena Wachlevski; Rodrigo Silva da Costa; Jandson Lucas Camelo da Silva; Juan Lima; Adriana Maria Alves; Lorena B. Thaíza Fernandes; Judit K. Szabo (Biodiversity and Conservation, 2024)

Spatializing soil elemental concentration as measured by X-ray fluorescence analysis using remote sensing data - Nícolas Augusto Rosin; José A.M. Demattê; Hudson Wallace Pereira de Carvalho; Heidy Soledad Rodriguez-Albarracín; Jorge Tadeu Fim Rosas; Jean Jesus Novais; Ricardo S.D. Dalmolin; Marcelo Rodrigo Alves; Renan Falcioni; Nikolaos Tziolas; Sina Mallah; Danilo César de Mello; et al. (CATENA, 2024)

Correction to: Role of Toll-like receptor 2 and 4 signaling pathways on the inflammatory response to resistance training in elderly subjects - Paula Rodriguez-Miguelez; Rodrigo Fernandez-Gonzalo; Mar Almar; Yubisay Mejías; Ana Rivas; José A. de Paz; María J. Cuevas; Javier González-Gallego (GeroScience, 2023)

Corrigendum to: “From waste to food and bioinsecticides: An innovative system integrating Tenebrio molitor bioconversion and pyrolysis bio-oil production” [Chemosphere 340 (2023)139847] - Rodrigo Iñaki Urrutia; Emiliano Nicolas Jesser; Victoria Soledad Gutierrez; Silvana Rodriguez; Fernanda Gumilar; Ana Paula Murray; Maria Alicia Volpe; Jorge Omar Werdin-González (Chemosphere, 2023)

From waste to food and bioinsecticides: An innovative system integrating Tenebrio molitor bioconversion and pyrolysis bio-oil production - Rodrigo Iñaki Urrutia; Emiliano Nicolas Jesser; Victoria Soledad Gutierrez; Silvana Rodriguez; Fernanda Gumilar; Ana Paula Murray; Maria Alicia Volpe; Jorge Omar Werdin-González (Chemosphere, 2023)

Two-step valorization of invasive species Rosa rubiginosa L. husk waste through eco-friendly optimized pectin extraction and subsequent pyrolysis - Rodrigo Torres-Sciancalepore; Mathias Riveros-Gomez; Daniela Zalazar-García; Daniela Asensio; María Paula Fabani; Rosa Rodriguez; Gastón Fouga; Germán Mazza (Journal of Environmental Chemical Engineering, 2023)

Life history and stock synthesis assessment of Prionotus punctatus (Teleostei, Triglidae) in southern Brazil - Andrea Renata Rodriguez; Manuel Haimovici; Eidi Kikuchi; Rodrigo Sant'Ana; Bruno L. Mourato; Jose Angel Alvarez Perez; Luís Gustavo Cardoso (Fisheries Management and Ecology, 2023)
Age, growth, and maturity of the bluewing searobin Prionotus punctatus were studied to assess its stock status in southern Brazil. Total length compositions, weight, sex, and maturity stage were recorded from commercial landings, and ages were estimated from transverse sections of the sagittal otolith. The oldest observed specimen was a 12‐year‐old female. Females grew to a larger asymptotic length ( L ∞ = 384.4 mm) than males ( L ∞ = 311.7 mm) but at a slower instantaneous rate ( k females = 0.41 year −1 , k males = 0.75 year −1 ). Reproduction occurred from spring to early fall. Females size‐ and age‐at‐maturity was estimated at 246.8 mm and 1.66 years, while males were at 237.2 mm and 1.38 years. Based on a statistical catch‐at‐age stock assessment, the spawning biomass declined 84% from 1976 to 2000 being classified as overfished and suffering from overfishing (B/B msy = 0.62; F/ Fmsy >1). P. punctatus was regularly discarded by industrial fisheries before 2000 but suffered from high exploitation in the last decades. These results highlight the need for the species to be included in Brazil's fishery management plans.

High Sugar Concentration Inhibits TOR Signaling Pathway in Arabidopsis thaliana - Cintia Pereyra; Rodrigo Parola; Ana Paula Lando; Marianela Rodriguez; Giselle María Astrid Martínez-Noël (Journal of Plant Growth Regulation, 2023)

Prediction ability for growth and maternal traits using SNP arrays based on different marker densities in Nellore cattle using the ssGBLUP - Juan Diego Rodriguez Neira; Elisa Peripolli; Maria Paula Marinho de Negreiros; Rafael Espigolan; Rodrigo López-Correa; Ignacio Aguilar; Raysildo B. Lobo; Fernando Baldi (Journal of Applied Genetics, 2022)

Conservation Policy Changes in Protected Areas on Hilltops in Brazil: Effects on Hydrological Response in a Small Watershed - Ulises Rodrigo Magdalena; Cristiane Nunes Francisco; Lucas Garofolo Lopes; Daniel Andrés Rodriguez (Water Resources Management, 2022)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Correction to: Summer phyto‑ and bacterioplankton communities during low and high productivity scenarios in the Western Antarctic Peninsula - Sebastián Fuentes; José Ignacio Arroyo; Susana Rodriguez‑Marconi; Italo Masotti; Tomás Alarcon‑Schumacher; Martin F. Polz; Nicole Trefault; Rodrigo De la Iglesia; Beatriz Díez (Polar Biology, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Automatic Adaptation of Model Neurons and Connections to Build Hybrid Circuits with Living Networks - Manuel Reyes-Sanchez; Rodrigo Amaducci; Irene Elices; Francisco B. Rodriguez; Pablo Varona (Neuroinformatics, 2020)

A simple model for the numerical characterization of spatiotemporal variability in aquatic ecosystems - Rodrigo Gonzalez-Valencia; Felipe Magaña-Rodriguez; Armando Sepulveda-Jauregui; Teresa Aguirrezabala-Campano; Oscar Gerardo-Nieto; Frederic Thalasso (Aquatic Sciences, 2019)

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Land cover change and carbon stores in a tropical montane cloud forest in the Sierra Madre Oriental, Mexico - Edgar G. Leija-Loredo; Numa P. Pavón; Arturo Sánchez-González; Rodrigo Rodriguez-Laguna; Gregorio Ángeles-Pérez (Journal of Mountain Science, 2018)

CO 2 exchange and evapotranspiration across dryland ecosystems of southwestern North America - Joel A. Biederman; Russell L. Scott; Tom W. Bell; David R. Bowling; Sabina Dore; Jaime Garatuza‐Payan; Thomas E. Kolb; Praveena Krishnan; Dan J. Krofcheck; Marcy E. Litvak; Gregory E. Maurer; Tilden P. Meyers; et al. (Global Change Biology, 2017)
Global‐scale studies suggest that dryland ecosystems dominate an increasing trend in the magnitude and interannual variability of the land CO 2 sink. However, such analyses are poorly constrained by measured CO 2 exchange in drylands. Here we address this observation gap with eddy covariance data from 25 sites in the water‐limited Southwest region of North America with observed ranges in annual precipitation of 100–1000 mm, annual temperatures of 2–25°C, and records of 3–10 years (150 site‐years in total). Annual fluxes were integrated using site‐specific ecohydrologic years to group precipitation with resulting ecosystem exchanges. We found a wide range of carbon sink/source function, with mean annual net ecosystem production ( NEP ) varying from ‐350 to +330 gC m −2 across sites with diverse vegetation types, contrasting with the more constant sink typically measured in mesic ecosystems. In this region, only forest‐dominated sites were consistent carbon sinks. Interannual variability of NEP , gross ecosystem production ( GEP ), and ecosystem respiration (R eco ) was larger than for mesic regions, and half the sites switched between functioning as C sinks/C sources in wet/dry years. The sites demonstrated coherent responses of GEP and NEP to anomalies in annual evapotranspiration ( ET ), used here as a proxy for annually available water after hydrologic losses. Notably, GEP and R eco were negatively related to temperature, both interannually within site and spatially across sites, in contrast to positive temperature effects commonly reported for mesic ecosystems. Models based on MODIS satellite observations matched the cross‐site spatial pattern in mean annual GEP but consistently underestimated mean annual ET by ~50%. Importantly, the MODIS ‐based models captured only 20–30% of interannual variation magnitude. These results suggest the contribution of this dryland region to variability of regional to global CO 2 exchange may be up to 3–5 times larger than current estimates.

Intense drought and flooding events in the Rio Negro and relation with the tropical Pacific and Atlantic variability modes - Rita Valéria Andreoli; Simone Nazaré Rodriguez da Silva; Rodrigo Augusto Ferreira de Souza; Mary Toshie Kayano; Sâmia Regina Garcia; Vinícius Buscioli Capistrano; Elisa Armijos (Theoretical and Applied Climatology, 2017)

Gluten ataxia is better classified as non-celiac gluten sensitivity than as celiac disease: a comparative clinical study - Luis Rodrigo; Carlos Hernández-Lahoz; Eugenia Lauret; Maria Rodriguez-Peláez; Miroslav Soucek; Rachele Ciccocioppo; Peter Kruzliak (Immunologic Research, 2016)

Genetic background of novel sequence types of CTX-M-8- and CTX-M-15-producing Escherichia coli and Klebsiella pneumoniae from public wastewater treatment plants in São Paulo, Brazil - Milena Dropa; Nilton Lincopan; Livia C. Balsalobre; Danielle E. Oliveira; Rodrigo A. Moura; Miriam Rodriguez Fernandes; Quézia Moura da Silva; Glavur R. Matté; Maria I. Z. Sato; Maria H. Matté (Environmental Science and Pollution Research, 2016)

Could coenzyme Q10 supplementation have a role in the treatment of anti-NMDA receptor encephalitis? - Ricardo Rangel-Guerra; Carlos Rodrigo Camara-Lemarroy; Gisela Garcia-Arellano; Ana Catalina Rodriguez-Martinez; Dionicio Angel Galarza-Delgado (Acta Neurologica Belgica, 2015)

Lithothamnion steneckii sp. nov. and Pneophyllum conicum: new coralline red algae (Corallinales, Rhodophyta) for coral reefs of Brazil - Rodrigo Mariath; Rafael Riosmena-Rodriguez; Marcia Figueiredo (Algae, 2012)

The activity of leech motoneurons during motor patterns is regulated by intrinsic properties and synaptic inputs - C. Bernardo Perez-Etchegoyen; Rodrigo J. Alvarez; Mariano J. Rodriguez; Lidia Szczupak (Journal of Comparative Physiology A, 2012)

Seroprevalence of Neospora caninum antibodies in beef cattle in three southern states of Mexico - Zeferino Garcia-Vazquez; Rodrigo Rosario-Cruz; Felix Mejia-Estrada; Ivan Rodriguez-Vivas; Dora Romero-Salas; Manuel Fernandez-Ruvalcaba; Carlos Cruz-Vazquez (Tropical Animal Health and Production, 2009)

Development of a citrus genome-wide EST collection and cDNA microarray as resources for genomic studies - J. Forment; J. Gadea; L. Huerta; L. Abizanda; J. Agusti; S. Alamar; E. Alos; F. Andres; R. Arribas; J. P. Beltran; A. Berbel; M. A. Blazquez; et al. (Plant Molecular Biology, 2005)